Protective capacity of Rutin against oxidative damage induced by saline stress in the roots of the model organism Allium cepa - Carlos Alonso Leite dos Santos; Antonia Adeublena de Araújo Monteiro; Patric Anderson Gomes da Silva; Jean Paul Kamdem; Antonia Eliene Duarte; Mashal M. Almutairi; Abid Ali; Saeed Anwar; Mohammad Ibrahim (Scientific Reports)
Abstract Salt stress limits plant growth by impairing physiological and biochemical processes, especially in roots, which are the main absorption organs. This study aimed to evaluate the phytoprotective potential of rutin against NaCl-induced salt stress in Allium cepa, focusing on morphological, biochemical, and molecular responses. Seeds were treated with 512 µg/mL and 1024 µg/mL rutin, both with 50 mM NaCl, and compared to a control group (NaCl only). Germination rate, root development, oxidative stress markers (TBARS, non-protein thiols, protein thiols), and elemental analysis of iron accumulation were measured. Rutin’s effects were also analyzed using in silico molecular docking with the Allium cepa cytokinin-specific binding protein (PDB: 5VGL). The results showed that rutin (512 µg/mL) combined with NaCl reduced germination rate and root development, while 1024 µg/mL rutin + NaCl mitigated salt-induced damage, improving germination speed, leaf number, and reducing oxidative stress markers, particularly in roots. Elemental analysis revealed reduced iron accumulation in the 1024 µg/mL rutin + NaCl group. In molecular docking, rutin (– 8.8 kcal/mol) showed strong interactions with the target protein, forming hydrogen bonds and amide-π stacking interactions, suggesting its protective role. These findings demonstrate that rutin exerts a dose-dependent phytoprotective effect, particularly in roots, and highlights its potential as a natural compound to mitigate salinity stress in plants.